Sosialisasi Situs Sejarah Rumah Tgk Chiek Awee Geutah sebagai Cagar Budaya dan Destinasi Wisata Religius Melalui Penyebaran Informasi Digital - Muslihin, Muslihin; Wahyudi, Wahyudi; A Rahman, Aisyah; Rahmi, Rahmi; Barona, Cucut Satria; Khairunnisa, Khairunnisa; Iwana, Cut; Izzatunnisa, Izzatunnisa; Hanum, Umaiza (Al-Qalam Institute, 2022)
The Tgk Chik Awee Geutah housing complex is very appropriate to be used as a cultural heritage site by the government to preserve Aceh's cultural heritage. In the complex of Tgk Chik Awee Geutah's house there is Tgk Chik Awee Geutah's grave, then there is also Balee Kalut which is south of Tgk Chik Awee Geutah's house. Balee Kalut is not far from the Tomb, Balee Kalut is a building in the form of an octagonal pyramid in the form of a stage. This place is a place of worship to Allah Almighty to cleanse all sins. Visitors/tourists who come apart from visiting Tgk Chik Awee Geutah's house also make pilgrimages to the tombs and some perform religious services. Therefore, this place can be used as a religious tourism destination. The current generation is considered less familiar with the local wisdom of their own region. The Cultural Heritage Site of Tgk Chik Awee Geutah's house needs to be preserved, one of which is by introducing this cultural heritage to the community and students, of course. By introducing the wisdom of Tgk Chik Awee Geutah's house, it is hoped that the current generation will know and know the identity of their ancestral heritage, by knowing and knowing them they will love the cultural heritage of their ancestors and then by loving it will protect and preserve this cultural heritage site. As for introducing this cultural heritage site using digitization, namely taking pictures and making videos of Tgk Chik Awee Geutah's house and also making learning videos that teachers can use later.